BBQ sauces, rubs & marinades for dummies / Traci Cumbay, Tom Schneider - Cumbay, Traci
This book is for the amateur BBQ enthusiast looking to increase his or her skill on the BBQ. This book showcases over 100 recipes for sauces rubs and marinades that he or she can quickly and easily assemble.